Upper Gastrointestinal Fiberoptic Endoscopic Experience in Turkey - K. Bahri ATEŞ; A. Remzi DALAY; Sedat BOYACIOĞLU; M. Emin CANER; M. Enver DOLAR; Fatih HİLMİOĞLU and Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2020)
-